THE METHOD OF FORMING JUNIOR HIGH SCHOOL EFL LEARNERS’ COMPETENCE IN LISTENING TO AND READING TEXTS - Romanyshyn, Ihor; Yatsiv, Svitlana (Mountain School of Ukrainian Carpaty, 2022)
The article reveals the theoretical aspects of learning English and its place and role in modern education. The main tasks and content of profilisation are determined. The methods of reading and listening to the texts while learning English and ways of improving them are studied. Nowadays, school profilisation is one of the important directions of Ukrainian general education modernisation. The introduction of subject-oriented instruction in the junior (1st-4th) grades of general educational institutions is determined by the current trends in the national education development, the state and society social services commissioning to school, the socio-economic and socio-cultural development of Ukraine, as well as by the analysis of the successful practices of foreign countries’ school education. The theoretical basis for the subject-oriented instruction implementation is the Laws of Ukraine “On Education” and “On General Secondary Education”, the Concept of Subject-Oriented Instruction in Junior School, the State Standard of Basic and Complete General Secondary Education and other regulatory documents. The main theoretical advances of domestic and foreign scientists with reference to the best practices in junior students’ education organisation are embodied in the Concept of Subject-Oriented Instruction in Primary School. Keywords: profilisation, foreign language activity, authentic speech, monologue speech, foreign language communicative competence, reading and listening skills, literary and colloquial speech.